The effects on children's literacy skills of reading e-books with different features: Are 'bells and whistles' over-rated? - Karemaker, A; Jelley, F; Clancy, C; Sylva, K (Elsevier, 2017)
Children’s literacy skills in schools and at home are widely supported by technologies designed to advance their development. Surprisingly, the unique effects of specific interface features are widely disputed and inconsistent research findings make it challenging to generalise across different technologies. It is difficult to make an informed choice about which types of e-books, and which specific features, are most effective. This small-scale, experimental study examines the unique effects of specific interface features and compares them to a Flat e-book. In a pre- and post-test comparison design, we investigated the effects of three different e-book conditions 1) ‘Flat’ e-book, 2) ‘E- friend’, and 3) ‘Dictionary’. Ninety typically developing Year-1 readers were selected from nine primary schools in England and then randomly assigned to one of the experimental groups. Results showed that children in the ‘Dictionary’ group increased more in Word Recognition of target words compared to the children in the ‘E-friend’ group. However, children in the ‘E-friend’ group made significantly greater gains in Reading Comprehension than children in the ‘Dictionary’ group. Children in the ‘Flat e-book’ performed as well on all measures as children in the enhanced features groups. We suggest new directions for research on features that might be superior to Flat e-books.